Hubungan Antara Kekerasan Psikologis Guru Dengan Self-Esteem dan Tingkat Stres Siswa SMK “X” Kabupaten Bandung (Jurusan Bimbingan dan Konseling Islam, 2015)
Psychological violence has characteristics disguise himself and sometimes becomes an ideology which justified as protection measures for the benefit of students. Nevertheless, violence in any form contrary to the educational foundation, so this study aims to identify the relationship of psychological violence that teachers do with self-esteem and stress levels of vocational studentsl. The method used is correlational research. The research sample of 146 students of class XI of SMK majoring in Software Engineering